A Consumer’s Guide to Eggs - Jeanine Beatty; Karla Shelnutt; Gail P. A. Kauwell (EDIS)
People have been eating eggs for centuries. Records as far back as 1400 BC show that the Chinese and Egyptians raised birds for their eggs. The first domesticated birds to reach the Americas arrived in 1493 on Christopher Columbus' second voyage to the New World. Most food stores in the United States offer many varieties of chicken eggs to choose from — white, brown, organic, cage free, vegetarian, omega-3 fatty acid enriched, and more. The bottom line is that buying eggs is not as simple as it used to be because more choices exist today. This 4-page fact sheet will help you understand the choices you have as a consumer, so you can determine which variety of egg suits you and your family best. Written by Jeanine Beatty, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, November 2013. http://edis.ifas.ufl.edu/fy1357